A practical approximation of pollen dispersal–deposition for calculation of pollen productivity and quantification of vegetation. Issue 6 (2nd November 2018) - Sjögren, Per; Van der Knaap, W. O.; VAN LEEUWEN, Jacqueline F. N.
Abstract: We compared simple mathematical pollen dispersal–deposition models with Gaussian plume models. The simple mathematical models proved equal or better approximations of real world pollen dispersal–deposition. We concluded that for most standard applications, such as estimating pollen productivity or quantitative vegetation reconstructions, simple mathematical models would perform satisfactory. Such easy-to-use models may lower the threshold to employ quantitative tools to palaeoecological questions.